2021
DOI: 10.3389/fimmu.2021.634435
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune Checkpoint Molecules for Relapse After Allogeneic Hematopoietic Cell Transplantation

Abstract: Immune checkpoint molecules represent physiological brakes of the immune system that are essential for the maintenance of immune homeostasis and prevention of autoimmunity. By inhibiting these negative regulators of the immune response, immune checkpoint blockade can increase anti-tumor immunity, but has been primarily successful in solid cancer therapy and Hodgkin lymphoma so far. Allogeneic hematopoietic cell transplantation (allo-HCT) is a well-established cellular immunotherapy option with the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…In the last few decades, immunotherapy has emerged as the fourth pillar following surgery, radiation/chemotherapy and targeted therapy for solid tumor and leukemia therapy. One of the most effective immunotherapies includes resolving T cell dysfunction with immune checkpoint (IC) inhibitors (ICIs), such as programmed death receptor-1 (PD-1) and its ligand (PD-L1), cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), and T cell immunoglobulin mucin-3 (Tim-3) (1)(2)(3)(4)(5). IC proteins are co-inhibitory receptors that distributed on the surface of several immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, immunotherapy has emerged as the fourth pillar following surgery, radiation/chemotherapy and targeted therapy for solid tumor and leukemia therapy. One of the most effective immunotherapies includes resolving T cell dysfunction with immune checkpoint (IC) inhibitors (ICIs), such as programmed death receptor-1 (PD-1) and its ligand (PD-L1), cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), and T cell immunoglobulin mucin-3 (Tim-3) (1)(2)(3)(4)(5). IC proteins are co-inhibitory receptors that distributed on the surface of several immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 24 articles evaluated the benefit of checkpoint inhibitors before or after allo-HSCT in different hematological malignancies and revealed that adding checkpoint blockers before or after allo-HSCT leads to higher rate of chronic, acute and hyperacute GVHD. T cells with low expression of PD-1 persist for 10 months or more leading to a higher risk of GVHD [99]. Several studies, especially in cHL, showed that PD-1 inhibitors are highly efficient in the relapsed setting, after allo-HSCT, at the cost of a higher rate of GVHD [96,98,100].…”
Section: Results In Amlmentioning
confidence: 99%
“…Loss of GVL effect is generally accountable to the relapse after allo-HSCT, which leads to tumor cells escaping from allogeneic immune response ( 12 , 35 ). With the clinical breakthrough of ICIs, boosting the GVL effect with ICIs post-allo-HSCT has become an appealing concept to treat relapse and improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is understandable that ICIs may potentially trigger uncontrollable immune breakthrough events, in particular severe GVHD, in the post-transplant setting ( 20 , 35 , 40 ). Therefore, the major obstacle with ICIs is to control the severity of GVHD while maintaining the GVL effect.…”
Section: Discussionmentioning
confidence: 99%